2022
DOI: 10.12669/pjms.38.4.4835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bronchofiberscopic lavage with budesonide suspension on refractory mycoplasma pneumoniae pneumonia

et al.

Abstract: Objectives: To investigate the clinical efficacy of budesonide suspension through bronchofiberscopic lavage in the treatment of refractory mycoplasma pneumoniae pneumonia (RMPP). Methods: A total of 108 children with refractory mycoplasma pneumoniae pneumonia from June 2018 to October 2020 were randomly divided into two groups: the study group and the control group, with 54 cases in each group. Children in the control group were treated with anti-infective, antitussive, antipyretic routine symptomatic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“… 18 The long-term combined delivery of drugs through co-suspension drug delivery technology can exert the effects of relaxing bronchial smooth muscle, regulating spasm, and expanding the airway by inhibiting the activation of bronchial smooth muscle β2 receptor, bronchial smooth muscle M3 acetylcholine receptor, and providing anti-inflammatory effects. 17 , 19 At the same time, there are certain differences in the density of β2 receptors and M3 acetylcholine receptors in the peripheral and central airways of the lung. Therefore, taking budesonide can also relax the smooth muscle of the peripheral and central airways, which is conducive to further regulating lung function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 The long-term combined delivery of drugs through co-suspension drug delivery technology can exert the effects of relaxing bronchial smooth muscle, regulating spasm, and expanding the airway by inhibiting the activation of bronchial smooth muscle β2 receptor, bronchial smooth muscle M3 acetylcholine receptor, and providing anti-inflammatory effects. 17 , 19 At the same time, there are certain differences in the density of β2 receptors and M3 acetylcholine receptors in the peripheral and central airways of the lung. Therefore, taking budesonide can also relax the smooth muscle of the peripheral and central airways, which is conducive to further regulating lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, taking budesonide can also relax the smooth muscle of the peripheral and central airways, which is conducive to further regulating lung function. 19 , 20 The combined BGF MDI can enhance the ability to jointly resist lung injury, and improve smooth muscle reactivity, and respiratory muscle strength. Research by Heo YA et al 18 also confirmed that among BGF MDI components, formoterol fumarate can relax smooth muscle and effectively alleviate bronchospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were incorporated into the analysis according to the following criteria in line with the PICOS framework: Participants: pediatric patients diagnosed with mycoplasma pneumonia; Interventions: inhaled budesonide in combination with azithromycin and azithromycin alone; Comparisons: assessing both efficacy and safety; Outcome measures: studies needed to report one or more of the following endpoints: total effective rate, adverse reactions, time for body temperature normalization, the time of disappearance of rales in the lungs, the time of disappearance of cough, pulmonary function, and inflammatory Jianbin et al [12] 2021 2018-2020 14 d 26 26 4.08 ± 1.47 4.52 ± 1.78 Intravenous Inhalation Naiju [13] 2021 2019-2020 14 d 30 30 6.60 ± 1.71 6.71 ± 1.80 Intravenous Inhalation Li and Yan [14] 2023 2021-2022 14 d 44 44 7.2 ± 1.4 6.7 ± 1.6 Intravenous Inhalation Hongbin [15] 2022 2020-2022 14 d 40 40 9.62 ± 1.34 9.95 ± 1.28 Intravenous Inhalation Zhou Yinhong [35] 2022 2019-2022 14 d 51 50 7.79 ± 2.12 7.84 ± 2.05 Intravenous Inhalation Xinyi [16] 2022 2020-2022 Not report 32 33 10.21 ± 3.36 9.68 ± 3.22 Intravenous Inhalation Linyun et al [17] 2023 2020-2022 7 d 31 31 7.00 ± 2.00 7.00 ± 2.33 Intravenous Inhalation Zhongzheng [18] 2022 [19] 2020 2017-2018 7 d 28 28 4.5 ± 1.4 4.8 ± 1.5 Intravenous Inhalation Xin et al [20] 2022 Not report 14 d 50 50 9.69 ± 2.77 9.32 ± 2.82 Intravenous Inhalation Wei et al [21] 2022 2018-2021 14 d 40 40 7.01 ± 1.48 6.92 ± 1.54 Intravenous Inhalation Di [22] 2022 2019-2020 10 d 41 41 4.6 ± 2.4 5.1 ± 2.0 Intravenous Inhalation Shangqing [23] 2022 2019-2020 14 d 43 43 3.04 ± 0.18 3.02 ± 0.21 Intravenous Inhalation Chunsun et al [24] 2020 2018-2019 7 d 48 48 6.84 ± 2.25 6.77 ± 2.10 Intravenous Inhalation Bo [25] 2022 [26] 2022 2016-2020 14-21 d 115 115 4.5 ± 1.1 6.5 ± 1.4 Intravenous Inhalation Jinglei et al [27] 2022 2018-2021 14 d 50 50 5.94 ± 0.85 5.96 ± 0.88 Intravenous Inhalation Li et al [28] 2023 2020-2021 10 d 100 100 4.72 ± 2.87 4.35 ± 2.28 Sequential Inhalation Zhishun and Yongchao [29] 2019 2017-2019 7 d 67 67 3.1 ± 0.7 3.4 ± 0.7 Sequential Inhalation Yanchun and Qiong [30] 2022 2020-2021 15 d 49 49 7.53 ± 1.19 7.29 ± 1.12 Sequential Inhalation Jianwei [31] 2022 2020-2021 21 d 34 34 7.98 ± 2.34 8.03 ± 2.37 Oral Inhalation Wenwen et al [32] 2023 2020-2022 7 d 60 60 5.08 ± 2.25 5.14 ± 2.23 Oral Inhalation Dali et al [...…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“… 4 However, the overall effect of the drug is not sufficient when used alone. 4 , 5 Recent studies have found that the onset and progression of COPD has a certain correlation with the intestinal microenvironment. 6 , 7 Research has shown that microbial colonies are not only distributed in the intestines, but also in the lungs, with a “gut-lung” axis connection.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Therefore, early implementation of safe and effective treatment for COPD is of great significance.Budesonide, a glucocorticoid anti-inflammatory drug, is used currently in clinical practice for the treatment of COPD, and can alleviate clinical symptoms to a certain extent. 4 However, the overall effect of the drug is not sufficient when used alone. 4,5 Recent studies have found that the onset and progression of COPD has a certain correlation with the intestinal microenvironment.…”
mentioning
confidence: 99%